High Accuracy Geodetic Control Point Measurement Using GPS Geodetic With Static Methods - Julianto, Eko Nugroho; Safrel, Ispen; Taveriyanto, Arie (Jurnal Teknik Sipil dan Perencanaan, 2018)
Abstract. The quality of the coordinates of the points in a generally horizontal control network will be influenced by many factors, such as the system equipment used for measuring / observation, the network geometry, measurement strategies / observation, as well as data processing strategy implemented. Using development of the GPS satellite system, since 1989, the network provision of horizontal control points in Indonesia generally relies on the GPS satellite observations. One way of measuring geodetic control points with high accuracy is using geodetic GPS. Measurement of geodetic control points required as a control in the execution of the work and as a correction coordinate measurement of the position of a measurement object with a high degree of accuracy (± 1 cm). How many measurement methods that can be done. This research conducted measurement using static method. Static surveys are used to determine the coordinates of the control points are relatively distant from each other as well as order accuracy requires relatively higher. The measurement results obtained coordinate data for point 1 is 6 ° 57 '31.92207 "LS; 109 ° 38 '32.25194 "BT; high (ellipsoid) 34 320 m and point 2 is 6 ° 57 '33.59086 "LS; 109 ° 38 '37.87710 "BT; high (ellipsoid) 36 235 m.